The Effect of Digital Sharing Technologies on Music Markets: A Survival Analysis of Albums on Ranking Charts - Bhattacharjee, Sudip; Gopal, Ram D.; Lertwachara, Kaveepan; Marsden, James R.; Telang, Rahul (Management Science, 2007)
Recent technological and market forces have profoundly impacted the music industry. Emphasizing threats from peer-to-peer (P2P) technologies, the industry continues to seek sanctions against individuals who offer a significant number of songs for others to copy. Combining data on the performance of music albums on the Billboard charts with file sharing data from a popular network, we assess the impact of recent developments related to the music industry on survival of music albums on the charts and evaluate the specific impact of P2P sharing on an album's survival on the charts. In the post-P2P era, we find significantly reduced chart survival except for those albums that debut high on the charts. In addition, superstars and female artists continue to exhibit enhanced survival. Finally, we observe a narrowing of the advantage held by major labels. The second phase of our study isolates the impact of file sharing on album survival. We find that, although sharing does not hurt the survival of top-ranked albums, it does have a negative impact on low-ranked albums. These results point to increased risk from rapid information sharing for all but the “cream of the crop.”